1951
DOI: 10.1103/physrev.83.1051.2
|View full text |Cite
|
Sign up to set email alerts
|

Electron Mobilities in Liquid Argon

Abstract: 0.88 0.65 85% -0 FIG. 2. Disintegration scheme of Os 186 .and the disintegration scheme are correct, the atomic mass difference between Os 185 and Re 185 may be estimated. This turns out to be about 1.0 Mev if the transition to the 0.88-Mev level is assumed to be first-forbidden, and slightly lower for an allowed transition.The fraction of the total K capture to the ground state has been reported 8 to be no greater than 0.10. The amount of L capture feeding the excited states could not be estimated at that tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1959
1959
1984
1984

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…However, as has been shown (Kopylov 1964), liquid flow should tend to become independent of E d when Im is small, and since the characteristics of figure 9, which extend to low currents, are strikingly similar, it would appear that the variation of ci is probably due to the mobility p varying as Ed-112. Malkin and Schultz (1951) using a single 'a' pulse method also found that the mobility of a negative carrier in argon varied inversely as the square root of the field. At that time the carrier was considered to be a free electron, but the suggestion has since been made that it was more likely to be a negative impurity ion (Swan 1960).…”
Section: Zon Mobilitiesmentioning
confidence: 93%
See 1 more Smart Citation
“…However, as has been shown (Kopylov 1964), liquid flow should tend to become independent of E d when Im is small, and since the characteristics of figure 9, which extend to low currents, are strikingly similar, it would appear that the variation of ci is probably due to the mobility p varying as Ed-112. Malkin and Schultz (1951) using a single 'a' pulse method also found that the mobility of a negative carrier in argon varied inversely as the square root of the field. At that time the carrier was considered to be a free electron, but the suggestion has since been made that it was more likely to be a negative impurity ion (Swan 1960).…”
Section: Zon Mobilitiesmentioning
confidence: 93%
“…There have been several reports of the mobility of positive and negative ions in liquefied argon, and in common with most dielectric liquids the values lie in the range 10-3-10-4 cm2 v-1 s-1. A second negative charge carrier has also been detected, which is probably a quasi-free electron with an apparent mobility which can exceed 102 cm2 v-1 s-1 (Davidson and Larsh 1948, 1950, Hutchinson 1948, Marshall 1954, Malkin and Schultz 1951, Williams 1957, Swan 1964, Schnyders et al 1965. In these measurements primary ionizing radiation is used to release electrons and positive ions.…”
Section: Introductionmentioning
confidence: 99%
“…This is the dependence reported by Malkin and Schultz (1951), but it is evident that the recent, more exhaustive work of Williams (1957) is correct on this point and therefore that kinetic theory is not applicable to the problem. This theory could in principle be extended to explain a fieldindependent velocity, by supposing a special dependence upon electron energy of the scattering cross section for the collision of electrons with argon atoms, but this is very artificial and unnecessary in view of the alternative explanation suggested here; in any case it leaves further serious objections, which will also be discussed briefly.…”
Section: Electron Mobility In Liquid Argon* By F D Staceytmentioning
confidence: 73%